Mosaiking of ERS SAR quicklook imagery of south east Asia - Kwoh, LK (I E E E, 2023)
1997 International Geoscience and Remote Sensing Symposium (IGARSS 97) on Remote Sensing - A Scientific Vision for Sustainable Development